2019
DOI: 10.3389/fmicb.2019.00904
|View full text |Cite
|
Sign up to set email alerts
|

The Fluoroquinolone Finafloxacin Protects BALB/c Mice Against an Intranasal Infection With Francisella tularensis Strain SchuS4

Abstract: The efficacy of the novel fluoroquinolone finafloxacin was evaluated as a potential therapeutic in vitro and in vivo , following an intranasal infection of Francisella tularensis strain SchuS4 in BALB/c mice. We demonstrated that short treatment courses of finafloxacin provide high levels of protection, with a single dose resulting in a significant increase in time to death when compared to ciprofloxacin. In addition, following investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…The data set detailed in these studies demonstrates that finafloxacin has activity under both acidic and neutral conditions, with enhanced activity of finafloxacin in low-pH environments, where other antibiotics (including ciprofloxacin) have reduced activity. This has been demonstrated for all of the biodefense pathogens of interest and is in agreement with data generated by other groups (7, 8, 10, 11). The improved activity of finafloxacin compared to that of ciprofloxacin (a typical treatment for infections caused by B.…”
Section: Textsupporting
confidence: 91%
See 1 more Smart Citation
“…The data set detailed in these studies demonstrates that finafloxacin has activity under both acidic and neutral conditions, with enhanced activity of finafloxacin in low-pH environments, where other antibiotics (including ciprofloxacin) have reduced activity. This has been demonstrated for all of the biodefense pathogens of interest and is in agreement with data generated by other groups (7, 8, 10, 11). The improved activity of finafloxacin compared to that of ciprofloxacin (a typical treatment for infections caused by B.…”
Section: Textsupporting
confidence: 91%
“…The availability of formulations of finafloxacin that can be delivered orally and systemically makes finafloxacin a worthy alternative for the treatment of a range of infections. In addition to good safety and efficacy data obtained in patients suffering from complicated urinary tract infections and pyelonephritis, previous studies have also demonstrated efficacy against the biothreat agents Burkholderia pseudomallei and Francisella tularensis in vitro and in vivo (6, 911). The aim of this study was to further evaluate the in vitro activity of finafloxacin against larger strain panels of biodefense pathogens.…”
Section: Textmentioning
confidence: 96%
“…Finafloxacin provided a protective benefit when compared with ciprofloxacin when where finafloxacin and ciprofloxacin offered 96% and 60% protection (respectively) when delivered for 7 days and initiated at hours post-challenge (35).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Comparisons from 10 days post-challenge onwards in these mice were not made, as too many mice had succumbed to infection. (38,35). Although the route of infection was different, the LD50 of strain SCHU S4 by both routes is low (<10 CFU) (39,40).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation